Xác định bậc và cơ chế của phản ứng oxi hóa m-xylen trên xúc tác perovskit La0,7Sr0,3MnO3. - Huyền, Trần Thị Thu; Hiền, Nguyễn Thị Minh; Phú, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
In previous reports [1, 2], we presented the preparation and the catalytic properties of La0.7Sr0.3MnO3 perovskite in total oxidation of m-xylene. Obtained results showed that the La0.7Sr0.3MnO3 perovskite exhibits a good catalytic activity in total oxidation of m-xylene at relatively low reaction temperature. In present work, we determined the kinectic characteristics of this reaction. The obtained results demonstrated that the reaction order value with respect to m-xylene is equal to about 1 and to oxygen is proximately equal to 0. Based on reaction order data, it was thought that the pathway of m-xylene oxidation by air oxygen over La0.7Sr0.3MnO3 may be followed through which the Langmuir - Hinshelwood mechanism.